Enhancement of the Cyclability of a Si/Graphite@Graphene composite as anode for Lithium-ion batteries - Su, Mingru; Wang, Zhixing; Guo, Huajun; Li, Xinhai; Huang, Silin; Xiao, Wei; Gan, Lei (Electrochimica acta, 2014)
•The composite has been prepared by an improved spray-drying method followed by heating treatment.•The structure of the composite is characterized and analyzed.•The composite exhibits high specific capacities and good cycle performances. Si/Graphite@Graphene composite has been prepared by an improved spray-drying method followed by heating treatment. While the thermal deposition of the precursor is determined by thermogravimetric analysis (TG-DTA), the structure of the composite is revealed by X-ray diffraction (XRD). Meanwhile, the presence of graphene is demonstrated by fourier transform infrared spectra (FI-IR) and Raman spectra studies. And scanning electron microscopy (SEM) and transmission electron microscope (TEM) images illustrate the morphology of the as-prepared material. The Si/Graphite@Graphene composite shows an enhanced electrochemical performance. At 50mAg−1, the Si/Graphite@Graphene sample exhibits a high initial charge capacity of 820.7 mAh g−1, with a high initial columbic efficiency of 77.98%, the composite can still deliver high initial charge capacity of 766.2 mAh g−1 at 500mAg−1, and shows superior cyclic and rate performance. Moreover, it has low impedance, which indicates that it could be used as a promising anode material for Li-ion batteries.